PENGARUH DURASI OZONASI DAN SUHU PENYIMPANAN TERHADAP KARAKTERISTIK CABAI MERAH KERITING (CAPSICUM ANNUUM L.) - Ni'mah, Miftahun
Red curly chili (Capsicum annuum L.) is one of the most popular horticultural products in Indonesia. Besides that, chili is also rich in vitamin C. Chili is perishable so it cannot be stored for a long time. There is a need for good postharvest handling to prolong the shelf life of chili. This study aims to determine the effect of variations in the duration of ozonation and storage temperature on the characteristics of curly red chili. The characteristics tested include water content, pH, total dissolved solids, vitamin C content, color, microbial, and hedonic level. This research Using Completely Randomized Design (RAL) with two testing stages and 3 repetitions. This research was started by optimizing the duration of ozonation (0, 5, 10 and 15 minutes) and then continued by testing the characteristics of curly red chili with the best ozonation treatment and stored at different temperatures (8 and 22 C). The results of the optimization of the duration of ozonation showed that the best ozonation duration was 15 minutes, which could reduce 87.1% of microbial colonies. The total APC of curly red chili with ozonation treatment 0 minutes, 5 minutes, 10 minutes and 15 minutes consecutive was 6.65; 6.49; 6.34 and 5.79 Log CFU/ml. The combination of 15 minute ozonation treatment with variations in storage temperature gave a significant effect on the characteristics of curly red chili. Curly red chili stored at cold temperatures has better characteristics, that is has a weight loss 0 - 21.42%, water content 74.24 - 76.85%, pH 4.96 - 5.23, TPT 3.23 - 4.07 % Brix, Vitamin C 18.31 - 51 .38 mg/100 gram, TPC 5.97 - 7.57 log CFU/ml and hedonic score of all attributes > 3 (preferred). Curly red chili stored at room temperature has a weight loss of 0 - 34.12%, moisture content of 63 ,04 - 76.85%, pH 5.02-5.24, TPT 3.13 - 4.8 %Brix, Vitamin C 11.81 - 51.38 mg/100 grams, TPC 5.97 - 7, 6 Log CFU/ml and preferred hedonic score (> 3) up to day 9 of storage.